67-g=40

Simple and best practice solution for 67-g=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 67-g=40 equation:


Simplifying
67 + -1g = 40

Solving
67 + -1g = 40

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-67' to each side of the equation.
67 + -67 + -1g = 40 + -67

Combine like terms: 67 + -67 = 0
0 + -1g = 40 + -67
-1g = 40 + -67

Combine like terms: 40 + -67 = -27
-1g = -27

Divide each side by '-1'.
g = 27

Simplifying
g = 27

See similar equations:

| 5y-4y=6 | | 2x+(k-2)x-(k+6)=0 | | 131=7x+5x-1 | | 2(r+1)=8 | | S(S-1)+7(S-1)=0 | | 7x-3+4x=-3 | | 3x+3=-6+6x | | 4x+28=10x-33 | | 4y-10=5y-15 | | 12y=-4(y+1) | | 4t^3-t=0 | | 138=-6x+5(x+26) | | d=120-4t | | 0.02x=0.45 | | 0.98x=0.45 | | 285=-7x-6(-5x-13) | | 2(k-4)=6 | | 11p=5p+2(10p-7) | | x*x+2*x+9=0 | | 2x=78+1 | | 2a/18ab | | h=-4.9t^2+50t+80 | | x*x*x*4+93*x*x+200*x+1000=0 | | -4(-7x+8)=-32 | | 2x+39=x-10 | | 4x-16=15x | | Z^2+2z+1=2i | | 4x^2+5=53 | | -10=-7x-17/8 | | 0.3=p-250 | | 10y=-5x+12 | | 4y+8y=180 |

Equations solver categories